Study on the use of polyanhydride as a therapeutic approach for the treatment of bone tissue injuries (Research, Society and Development, 2021)
Polyanhydride (PA) is a synthetic, biodegradable polymer that has an erosion mechanism that is very useful in the application of bone tissue regeneration. This study aimed to evaluate the evolution of scientific publications related to biodegradable polyanhydrides with their application in bone tissue regeneration. Searches were carried out in the journals databases of Web of Science and Scopus through the combination of keywords, and the results reported in the databases were tabulated. It was found that the number of publications occurred in the time frame from 1993 to 2019, with the largest number of publications belonging to the United States. It was also found that pharmacology, toxicology and pharmaceuticals (18%), immunology and microbiology (13%) and chemical engineering (13%) were the most prominent areas, with 46% of publications referring to original articles and 39% review articles. The high impact of publications in this area was evidenced by the increasing number of citations, reinforcing the productivity and notoriety of the theme before researchers. It can be concluded, therefore, that this is an area of research that has been experiencing notable growth, showing its promising character.